An epidemiological study of depression among college students in district Faridkot, Punjab, India - Padda, Preeti; Gupta, Sanjay; Singh, Gaganpreet; Singh, Lakhwinder; Chawla, Narail (Indian Journal of Community Health, 2016)
Background: Depression is one of the most under diagnosed and under reported in primary health settings. Depression is highly common and according to WHO by 2020, it would be the second-most prevalent condition worldwide. Physical illnesses and bio-psychosocial factors are common determinants of depression. Aims & Objectives: 1. To estimate prevalence of depression, 2. To determine associated factors among college going students. Material & Methods: A descriptive cross-sectional study conducted among college going students. Half of the colleges were selected randomly and sample size was distributed on the basis of probability proportional to size (PPS). Assigned number of students from each college was selected by simple random sampling. Sample size of 1300 was calculated using formula (n) = ( Z1-? )2 P (100 - P ) / ?2. General Health Questionnaire (12 items) was used to diagnose psychiatric morbidity and those with this were administered Becks Depression Inventory II (21 items) scale for assessing the prevalence and level of depression. Both the scales were translated in local language and self-administered. The data was compiled and analyzed using Epi InfoTM. Results: A total of 1300 students were enrolled, psychiatric morbidity was present in 35% and prevalence of depression was 33%. Mild depression was found in 87% of the students with depression. Depression was higher among those aged >25 years, females, residing in nuclear families and studying science stream. Conclusion: Family support and adequate treatment are most important pillars of management.